A metal-doped silicon-based negative electrode material and its preparation method and application

By using metal-doped silicon-based anode material in lithium batteries, the cracking and powdering problems caused by volume changes of silicon materials are solved, and the good capacity performance and cycle stability of the material are achieved, and the service life and electrochemical performance of the battery are improved.

CN119297260BActive Publication Date: 2025-04-08NANCHANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411807220.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-08
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

When silicon materials are used in lithium batteries, due to huge volume changes, it is easy to cause negative electrode rupture and powderization, resulting in capacity loss and battery failure.

Method used

A metal-doped silicon-based negative electrode material is used, which forms a metal-doped silicon-based negative electrode material through multiple steps by mixing the surface-activated silicon-based negative electrode material with a metal organic frame nanosheet suspension, including coating solution treatment, transition metal solution treatment and high-temperature calcination, forming a material with good capacity performance and cycle stability.

Benefits of technology

The good capacity performance and cycle stability of the silicon-based negative electrode material are achieved, cracking and powdering problems caused by volume changes are avoided, and the service life and electrochemical performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297260B_ABST
    Figure CN119297260B_ABST
Patent Text Reader

Abstract

The present invention provides a metal-doped silicon-based negative electrode material and a preparation method and application thereof, and relates to the technical field of new energy battery materials. The preparation method provided by the present invention comprises: stirring and mixing the surface-activated silicon-based material in a metal organic framework nanosheet suspension and separating and drying to obtain a composite precursor; stirring and mixing the composite precursor in a coating solution and separating and drying to obtain a composite intermediate; stirring and mixing the composite intermediate in a transition metal solution, dripping an organic ligand, stirring and reacting, and separating and drying to obtain a doped intermediate; pre-sintering the doped intermediate in an oxygen-containing atmosphere at 100°C-150°C for 0.5h-1h, calcining and cooling in an inert atmosphere at 1000°C-1200°C to obtain a metal-doped silicon-based negative electrode material. The preparation method provided by the present invention is simple to operate, does not require the use of complex mechanical equipment, and the obtained metal-doped silicon-based negative electrode material has good capacity performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery materials, and in particular to a metal-doped silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] As one of the four main materials of lithium batteries, the performance of negative electrode materials has a key impact on battery performance. Since graphite has good cycle stability and excellent electrical conductivity, and the layered structure of graphite has good lithium insertion space, current lithium battery manufacturers mainly use graphite negative electrodes in lithium batteries. However, with the continuous improvement of the performance requirements for lithium batteries, the natural limitations of graphite negative electrodes (low theoretical gram-to-electricity capacity, easy peeling and shedding during long cycles, etc.) restrict the development of lithium batteries.

[0003] Silicon materials have a high theoretical specific capacity and have become a very promising negative electrode material. However, there are still some urgent problems to be solved when using silicon materials in lithium batteries. For example, the volume change of silicon materials is huge, which can easily lead to the cracking and pulverization of the negative electrode, causing huge capacity loss during the battery cycle, and even causing battery failure. At present, silicon materials are usually modified in their application in order to improve the volume expansion problem of silicon materials and increase the capacity of silicon materials.

[0004] The existing technology for modifying silicon materials is to compound them with carbon materials, metal materials or other materials with high conductivity. For example, compounding silicon materials and metal materials by high-energy ball milling can fully mix silicon and metal, but it will greatly destroy the morphological structure of silicon materials. Although it can improve the expansion problem of silicon materials, the actual specific capacity of the final material is still far lower than the theoretical specific capacity. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0005] The purpose of the present invention is to provide a metal-doped silicon-based negative electrode material and a preparation method and application thereof. The preparation method provided by the present invention is simple to operate and does not require the use of complex mechanical equipment. The prepared metal-doped silicon-based negative electrode material has good capacity performance and cycle stability.

[0006] In the first aspect, the present invention provides a method for preparing a metal-doped silicon-based negative electrode material, comprising: stirring and mixing the surface-activated silicon-based material in a metal organic framework nanosheet suspension, and separating and drying to obtain a composite precursor; stirring and mixing the composite precursor in a coating solution, and separating and drying to obtain a composite intermediate; stirring and mixing the composite intermediate in a transition metal solution, and then dropping an organic ligand and stirring for reaction, and then separating and drying to obtain a doped intermediate; pre-sintering the doped intermediate in an oxygen-containing atmosphere at 100°C-150°C for 0.5h-1h, and then calcining in an inert atmosphere at 1000°C-1200°C and cooling to obtain a metal-doped silicon-based negative electrode material.

[0007] Optionally, the preparation method of the silicon-based material includes: stirring and mixing silicon powder and cellulose, then carbonizing and crushing to obtain a silicon-carbon mixture; ultrasonically mixing the silicon-carbon mixture in an alcohol solution, adding a cross-linking agent, stirring and mixing, and then separating and drying to obtain a silicon-carbon composite; carbonizing the silicon-carbon composite at 600°C-700°C and crushing to obtain a silicon-based material.

[0008] Optionally, the mass ratio of the silicon powder to the cellulose is 1:(1-1.5).

[0009] Optionally, the silicon powder and cellulose are mixed and then carbonized and crushed at 10 MPa-50 MPa and 300° C.-400° C.

[0010] Optionally, the alcohol solution includes one of methanol and ethanol.

[0011] Optionally, the solid-to-liquid ratio of the silicon-carbon mixture in the alcohol solution is 0.05 g / mL-0.08 g / mL.

[0012] Optionally, the cross-linking agent includes one of 1,3-propanedithiol, 1,5-pentanedithiol, and 1,9-nonanedithiol.

[0013] Optionally, the mass ratio of the silicon-carbon mixture to the cross-linking agent is 1:(0.1-0.2).

[0014] Optionally, the average particle size of the silicon-based material is 50nm-100nm.

[0015] Optionally, the silicon-based material is surface-treated in a titanate coupling agent and / or a nitrogen-containing coupling agent to obtain a surface-activated silicon-based material.

[0016] Optionally, the titanate coupling agent includes one of triisostearoyl isopropyl titanate and isopropoxy tricarboxylic acid titanate.

[0017] Optionally, the nitrogen-containing coupling agent includes one of 3-piperazinepropylmethyldimethoxysilane and N-(aminoethyl)-3-aminopropylmethyldimethoxysilane.

[0018] Optionally, the silicon-based material is immersed in an active solution in which a titanate coupling agent and / or a nitrogen-containing coupling agent is dissolved, and then separated and dried to obtain a surface-activated silicon-based material.

[0019] Optionally, the mass ratio of the silicon-based material to the coupling agent is 1:(0.05-0.10), and the coupling agent is a titanate coupling agent and / or a nitrogen-containing coupling agent.

[0020] Optionally, the mass ratio of the surface activated silicon-based material to the metal organic framework nanosheets in the metal organic framework nanosheet suspension is 1:(0.1-0.2).

[0021] Optionally, the length of the metal organic framework nanosheets in the metal organic framework nanosheet suspension is 1 μm-10 μm and the thickness is 50 nm-200 nm.

[0022] Optionally, the solvent in the metal organic framework nanosheet suspension includes one of methanol and ethanol.

[0023] Optionally, the solute in the coating solution includes melamine.

[0024] Optionally, the mass ratio of the composite precursor to the solute in the coating solution is 1:(0.2-0.3).

[0025] Optionally, the composite precursor is stirred and mixed in a coating solution at 40°C-50°C.

[0026] Optionally, the composite precursor is dispersed in the coating solution by ultrasound.

[0027] Optionally, after the composite precursor is stirred and mixed in the coating solution, it is separated and dried in a vacuum environment at 60° C.-80° C.

[0028] Optionally, the transition metal element in the transition metal solution includes one of cobalt, copper, titanium, manganese, zinc, magnesium and platinum.

[0029] Optionally, the organic ligand includes one of 2-methylimidazole, terephthalic acid, and 2,5-thiophenedicarboxylic acid.

[0030] Optionally, the mass ratio of the composite intermediate, the transition metal element in the transition metal solution, and the organic ligand is 1:(0.2-0.3):(0.05-0.08).

[0031] Optionally, the volume fraction of oxygen in the oxygen-containing atmosphere is 10%-100%.

[0032] Optionally, the doped intermediate is heated to 100° C.-150° C. at a rate of 1° C. / min-10° C. / min in an oxygen-containing atmosphere.

[0033] Optionally, the doped intermediate is pre-sintered in an oxygen-containing atmosphere at 100° C.-150° C. for 0.5 h-1 h, and then heated to 1000° C.-1200° C. at a rate of 1° C. / min-10° C. / min in an inert atmosphere.

[0034] Optionally, calcination is performed at 1000° C.-1200° C. in an inert atmosphere for 2 h-3 h.

[0035] In a second aspect, the present invention also provides a metal-doped silicon-based negative electrode material prepared by any of the above optional preparation methods.

[0036] In a third aspect, the present invention further provides the use of the metal-doped silicon-based negative electrode material prepared by any of the above optional preparation methods in a lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A flowchart of a method for preparing a metal-doped silicon-based negative electrode material provided by the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0039] See also Figure 1 The present invention provides a method for preparing a metal-doped silicon-based negative electrode material, comprising:

[0040] S1, stirring and mixing the surface activated silicon-based material in the metal organic framework nanosheet suspension and separating and drying to obtain a composite precursor;

[0041] S2, stirring and mixing the composite precursor in the coating solution, and then separating and drying to obtain a composite intermediate;

[0042] S3, stirring and mixing the composite intermediate in a transition metal solution, adding an organic ligand dropwise and stirring for reaction, and then separating and drying to obtain a doped intermediate;

[0043] S4. Pre-sintering the doped intermediate in an oxygen-containing atmosphere at 100° C.-150° C. for 0.5 h-1 h, calcining in an inert atmosphere at 1000° C.-1200° C. and cooling to obtain a metal-doped silicon-based negative electrode material.

[0044] In fact, after the silicon-based material is subjected to surface activation treatment in step S1, the reaction activity of the silicon-based material surface can be effectively improved. When the metal organic framework nanosheet suspension is stirred, the shear force generated by the stirring promotes the adhesion of the metal organic framework nanosheet to the surface of the silicon-based material, thereby forming a nanosheet coating layer with a loose structure on the surface of the silicon-based material. At the same time, the stirring process is conducive to improving the uniformity of the nanosheet coating layer, thereby protecting the silicon-based material therein.

[0045] In some embodiments, the silicon-based material is surface treated in advance in step S1, including: surface treating the silicon-based material in a titanate coupling agent and / or a nitrogen-containing coupling agent to obtain a surface-activated silicon-based material. In fact, after the silicon-based material is surface treated with a titanate coupling agent and / or a nitrogen-containing coupling agent, different active groups can be introduced on the surface of the silicon-based material, which can effectively improve the dispersibility and interface bonding performance of the silicon-based material, and facilitate the attachment and coating of the metal organic framework nanosheets on the surface of the silicon-based material.

[0046] In some embodiments, when the silicon-based material is surface treated in advance, the titanate coupling agent used includes one of triisostearyl isopropyl titanate and isopropoxy tricarboxylic titanate. In fact, the molecules of the titanate coupling agent all have a titanium central atom, which can react and condense with the silicon-hydroxyl group on the surface of the silicon-based material to introduce a silicon-oxygen-titanium bond on the surface of the silicon-based material.

[0047] In some embodiments, when the silicon-based material is surface treated in advance, the nitrogen-containing coupling agent used includes one of 3-piperazinylpropylmethyldimethoxysilane and N-(aminoethyl)-3-aminopropylmethyldimethoxysilane. In fact, the nitrogen-containing coupling agent contains amino groups in its molecules, and because the amino groups have strong nucleophilicity, they can react with the hydroxyl groups on the silicon-based surface, thereby introducing silicon-oxygen-silicon bonds on the surface of the silicon-based material.

[0048] In fact, when the silicon-based material is surface treated in advance, a titanate coupling agent and a nitrogen-containing coupling agent can be used to compound, thereby increasing the richness of the surface active groups of the silicon-based material. Specifically, when the surface treatment is performed, the mass ratio of the silicon-based material to the coupling agent (titanate coupling agent and / or nitrogen-containing coupling agent) is 1: (0.05-0.10).

[0049] In some embodiments, when the silicon-based material is surface treated in advance, the silicon-based material is immersed in an active solution in which a titanate coupling agent and / or a nitrogen-containing coupling agent is dissolved, and then separated and dried to obtain a silicon-based material after surface activation. Specifically, immersing the silicon-based material in the active solution is conducive to the coupling agent fully contacting the silicon-based material, thereby facilitating the surface activation effect and the activation efficiency.

[0050] In fact, the silicon-based material can be added to the active solution and then dispersed and impregnated with ultrasound. This is helpful to avoid agglomeration and sedimentation of the silicon-based material during activation treatment, and can further improve the dispersion uniformity of the silicon-based material in the active solution, thereby improving the activation effect and efficiency.

[0051] In some embodiments, after the silicon-based material is immersed in the active solution, the solid-liquid separation can be performed by common separation means such as filtration separation and suction filtration separation, and then the obtained solid is dried in an environment of 30-60° C. to obtain the silicon-based material after surface activation. In fact, after obtaining the solid, it can also be rinsed with deionized water to remove impurities adhering to the surface.

[0052] Specifically, the preparation method of the silicon-based material used in step S1 includes: stirring and mixing silicon powder and cellulose, and then carbonizing and crushing to obtain a silicon-carbon mixture; ultrasonically mixing the silicon-carbon mixture in an alcohol solution, adding a cross-linking agent, stirring and mixing, and then separating and drying to obtain a silicon-carbon composite; carbonizing the silicon-carbon composite at 600°C-700°C and then crushing to obtain a silicon-based material.

[0053] In fact, when preparing silicon-based materials, mixing silicon powder and cellulose in advance is beneficial to improve the uniformity of dispersion between silicon powder and cellulose, so that after carbonization, cellulose can form a dense carbon network and anchor and coat silicon powder, thus forming a uniform silicon-carbon structure. At the same time, after the carbonized silicon powder and cellulose are crushed, it is beneficial to reduce the particle size of the silicon-carbon mixture, which is beneficial to increase the specific surface area and surface defects, thereby improving the reaction activity.

[0054] Specifically, when preparing silicon-based materials, the mixing ratio of silicon powder to cellulose is 1:(1-1.5). In fact, in the silicon-based materials formed by mixing silicon powder and cellulose within this ratio, the carbon network can anchor and connect the silicon powder well, thereby effectively improving the structural stability of the silicon-based materials, and at the same time balancing the volume change and theoretical energy storage capacity of the silicon-based materials during the charging and discharging process.

[0055] In some embodiments, when preparing silicon-based materials, silicon powder and cellulose are mixed and then carbonized and crushed at 10MPa-50MPa and 300°C-400°C. In fact, carbonization under high pressure is conducive to promoting close contact between silicon powder and cellulose, and can inhibit the release of gas during cellulose pyrolysis and form pores in the silicon-carbon material, which is conducive to improving the surface defects and reaction activity of the silicon-carbon material.

[0056] In fact, when preparing silicon-based materials, the silicon-carbon mixture is ultrasonically mixed in an alcohol solution, and the cavitation effect brought by ultrasound can be used to improve the dispersion uniformity of the silicon-carbon mixture in the alcohol solution, while avoiding the precipitation of the silicon-carbon mixture in the alcohol solution. In addition, by adding a cross-linking agent and stirring the reaction, the silicon powder and the carbon network surface in the silicon-carbon mixture can react, thereby improving the connection stability of the carbon network formed after the silicon powder and cellulose are carbonized.

[0057] Specifically, the alcohol solution used includes one of methanol and ethanol. In addition, the alcohol solution can also be a mixture of methanol, ethanol and deionized water, wherein the volume fraction of methanol and / or ethanol is greater than or equal to 50%. At the same time, the solid-liquid ratio in the suspension formed after the silicon-carbon mixture is dispersed in the alcohol solution is 0.05g / mL-0.08g / mL, which is conducive to the full dispersion of the silicon-carbon mixture.

[0058] Specifically, the cross-linking agent added during the preparation of the silicon-based material includes one of 1,3-propanedithiol, 1,5-pentanedithiol, and 1,9-nonanedithiol. In fact, since the added cross-linking agents all contain thiol, during the cross-linking reaction, the thiol can react with the active groups such as hydroxyl groups and unsaturated bonds on the surface of the silicon powder and the carbon network, thereby connecting the silicon powder and the carbon network. At the same time, it can also introduce some sulfur elements into the silicon-based material to form SC and S-Si bonds in the silicon-based material, which can improve the adaptability of the silicon-based material to volume changes during the charge and discharge process.

[0059] Specifically, when preparing the silicon-based material, the mass ratio of the added crosslinking agent to the silicon-carbon mixture dispersed in the alcohol solution is (0.1-0.2):1, which is conducive to the crosslinking agent to uniformly crosslink the silicon-carbon mixture. In fact, when the amount of the crosslinking agent is too small, the crosslinking points formed in the silicon-carbon mixture are relatively few, the formed crosslinking network is relatively sparse, the pores in the formed silicon-based material are large, and the structural stability is insufficient. When the amount of the crosslinking agent is too much, the crosslinking network formed in the silicon-carbon mixture is denser and the structural stability is stronger, but the pores are smaller and the ability to resist volume expansion changes is poor.

[0060] In some embodiments, when preparing silicon-based materials, the average particle size of the silicon powder used is 30nm-50nm, and the cellulose used is biomass cellulose, which can be specifically wheat straw cellulose with a particle size of 0.1mm-0.5mm and a water content of less than 10%. In addition, after the silicon-based material is prepared, it is carbonized and crushed, and the particle size of the silicon-based material collected is 50nm-100nm. In fact, by controlling the particle size of the silicon-based material, it is beneficial to increase its specific surface area, thereby providing more adsorption and embedding sites for lithium ions, which can effectively increase the battery capacity, and at the same time can also increase the diffusion rate of ions and reduce polarization. In addition, small-particle silicon-based materials can better alleviate the stress concentration caused by volume changes, thereby avoiding the splitting and pulverization of silicon-based materials during the charging and discharging process, and can effectively increase the service life of the negative electrode material.

[0061] Specifically, in step S1, the mass ratio of the silicon-based material after surface activation to the metal organic framework nanosheets in the metal organic framework nanosheet suspension is 1:(0.1-0.2). In fact, by regulating the amount of metal organic framework nanosheets, the coating amount, density and uniformity of the metal organic framework nanosheets on the surface of the silicon-based material can be regulated. In addition, pre-preparing the metal organic framework nanosheets into a suspension is conducive to improving the uniformity of the metal organic framework nanosheets, which is conducive to uniform loading on the surface of the silicon-based material.

[0062] Specifically, the length of the metal organic framework nanosheet used in step S1 is 1 μm-10 μm and the thickness is 50 nm-200 nm. In fact, when the metal organic framework nanosheet is compounded on the surface of the silicon-based material, a complex two-dimensional network structure can be formed on the surface of the silicon-based material through the mutual coverage, interlacing, entanglement and stacking between the metal organic framework nanosheets, which can provide ion transmission channels for lithium ions, thereby effectively improving the ion transmission efficiency. At the same time, the coating structure formed by the metal organic framework nanosheet can disperse the stress of the silicon-based material when the volume changes, thereby inhibiting the pulverization and structural damage of the silicon-based material due to the volume change, and effectively improving the cycle life of the negative electrode material.

[0063] Specifically, the metal ions in the metal organic framework nanosheets used in step S1 may be one of cobalt, copper, titanium, manganese, zinc, magnesium, and platinum. In fact, the metal organic framework nanosheets may be a mixture of metal organic framework nanosheets with multiple different metal elements as the core, thereby forming a coating structure with different metal cores on the surface of the silicon-based material, and then forming a skeleton doped with different metals after subsequent carbonization and calcination treatment, which is beneficial to comprehensively improve the conductivity and cycle stability of the negative electrode material.

[0064] In fact, the solvent in the metal organic framework nanosheet suspension used in step S1 includes one of methanol and ethanol. Specifically, in some embodiments, a coupling agent can also be added to the metal organic framework nanosheet suspension to improve the surface activity of the metal organic framework nanosheet and avoid agglomeration and sedimentation of the metal organic framework nanosheet in the suspension.

[0065] In some embodiments, the solute of the coating solution used in step S2 includes melamine. In fact, by stirring and mixing the composite precursor in the coating solution, it is beneficial for the solute in the coating solution to coat the surface of the metal organic framework nanosheet in the composite precursor, which can not only coat the metal organic framework coating layer, but also improve its surface activity, thereby facilitating the subsequent growth of metal organic framework nanomaterials on its surface, and modifying the pore structure of the metal organic framework nanosheet. At the same time, the solute in the coating solution, such as melamine, can also introduce nitrogen elements on the surface of the metal organic framework nanosheet.

[0066] In some embodiments, in step S2, the mass ratio of the composite precursor to the solute in the coating solution is 1:(0.2-0.3). In fact, by adjusting this mass range, the coating amount of the solute in the coating solution on the surface of the composite precursor can be controlled, thereby achieving uniform coating of the metal organic framework nanosheets on the composite precursor.

[0067] In some embodiments, the composite precursor is stirred and mixed in a coating solution at 40°C-50°C in step S2. In fact, coating treatment at 40°C-50°C is beneficial to improving the reactivity of the composite precursor and the solute in the coating solution, thereby ensuring that the solute in the coating solution forms a stable coating structure on the surface of the composite precursor, and mixing by stirring is beneficial to improving the coating uniformity. Specifically, the composite precursor can be ultrasonically dispersed in the coating solution.

[0068] In some embodiments, after the composite precursor is stirred and mixed in the coating solution in step S2, the solids can be separated by solid-liquid separation means commonly used in the art, such as filtration separation and suction filtration separation, and then dried in a vacuum environment at 60°C-80°C. In fact, during the drying process, the solute coated on the surface of the composite precursor can be promoted to combine with the metal organic framework nanosheets on the surface of the composite precursor, while preventing the composite precursor from cracking between the silicon-based material and the metal organic framework nanosheets during the drying process.

[0069] In fact, in step S3, the composite intermediate is stirred and mixed in the transition metal solution in advance, which is beneficial to promote the pre-binding of transition metal ions in the transition metal solution on the surface of the composite intermediate, and then after the organic ligand is added, metal organic framework nanoparticles can be generated in situ on the surface of the composite intermediate, and then the pore structure of the metal organic framework nanosheet can be modified, which is beneficial to improve the adaptability to volume changes, cycle stability and capacity performance.

[0070] In fact, since the coating solution is treated on the surface of the composite precursor, it is possible to avoid the metal organic framework particles growing along the shape of the surface metal organic framework nanosheets in step S3, and thus its pore structure cannot be modified, making it difficult to improve the cycle performance and capacity performance of the negative electrode material during use.

[0071] In some embodiments, the transition metal element in the transition metal solution used in step S3 includes one of cobalt, copper, titanium, manganese, zinc, magnesium, and platinum. In fact, by using different kinds of transition metal elements, metal organic framework nanoparticles of different forms can be grown on the surface of the composite intermediate, thereby modifying the metal organic framework nanosheets in different forms. Specifically, the transition metal element in the transition metal solution is the same as the metal element in the metal organic framework nanosheet, thereby forming homogeneous metal organic framework materials of different forms on the surface of the silicon-based material.

[0072] In some embodiments, the organic ligand used in step S3 includes one of 2-methylimidazole, terephthalic acid, and 2,5-thiophene dicarboxylic acid. In fact, the 2-methylimidazole molecule contains an imidazole ring structure, in which the nitrogen atom has arc pairs of electrons, which can form a coordination bond with the transition metal ion, thereby generating metal organic framework nanoparticles on the surface of the composite intermediate, and the terephthalic acid molecule has a benzene ring and two carboxyl groups, and the carboxyl groups can coordinate with the transition metal ions, thereby enabling one terephthalic acid molecule to coordinate with two transition metal ions, and the 2,5-thiophene dicarboxylic acid molecule contains a thiophene ring and two carboxyl groups, which can also coordinate with two transition metal ions.

[0073] Specifically, in step S3, zinc can be used as a transition metal and 2-methylimidazole as an organic ligand to generate 2-methylimidazole zinc salt (ZIF-8) in situ on the surface of the composite intermediate, and cobalt can be used as a transition metal to react with 2-methylimidazole to generate 2-methylimidazole cobalt (ZIF-67). In fact, the metal organic framework nanosheet used in step S2 can be a ZIF-8 nanosheet or a ZIF-67 nanosheet.

[0074] In some embodiments, in step S3, the mass ratio of the composite intermediate, the transition metal element in the transition metal solution, and the organic ligand is 1: (0.2-0.3): (0.05-0.08). In fact, by regulating the amount of the composite intermediate and the transition metal element, the amount of metal organic framework nanoparticles generated in situ on the surface of the composite intermediate can be controlled, thereby regulating the degree of modification of the pores. In fact, in step S3, the composite intermediate is dispersed into the transition metal solution, and the transition metal solution can fully penetrate into the surface pores of the composite intermediate, thereby achieving pre-filling of the transition metal ions.

[0075] In fact, in step S4, pre-sintering the doped intermediate at 100°C-150°C is beneficial to improving the bonding stability between the metal organic framework nanosheets and the metal organic framework nanoparticles. In addition, controlling the pre-sintering time to 0.5h-1.0h can avoid excessive oxidation of the doped intermediate, thereby affecting the electrochemical performance of the negative electrode material. Specifically, the oxygen volume fraction in the oxygen-containing atmosphere used is 10%-100%, and the oxygen-containing atmosphere can be clean air and oxygen.

[0076] In some embodiments, in step S4, the doped intermediate is placed in a furnace of a tube furnace, and heated to 100-150° C. at a heating rate of 1° C. / min-10° C. / min in an oxygen-containing atmosphere for heat preservation and pre-sintering. In fact, by controlling the heating rate, it is possible to avoid excessive temperature changes, which may lead to uneven heating of the doped intermediate, cracking, and pulverization.

[0077] In some embodiments, in step S4, the doped intermediate is pre-sintered in an oxygen-containing atmosphere at 100°C-150°C for 0.5h-1h, and then heated to 1000°C-1200°C at a rate of 1°C / min-10°C / min in an inert atmosphere for calcination for 2h-3h. In fact, calcination at 1000°C-1200°C is conducive to the diffusion and re-shooting of transition metal atoms in the doped intermediate, so that a more uniform metal-carbon skeleton can be formed on the surface of the silicon-based material, and at the same time, the metal-carbon skeleton can be cross-linked with the silicon-based material, thereby effectively improving the structural stability. In addition, calcination in an inert atmosphere can also prevent the silicon-based material from being severely oxidized, which is conducive to improving chemical stability and structural integrity.

[0078] The present invention also provides a metal-doped silicon-based negative electrode material prepared by the preparation method in any of the above embodiments, which includes a silicon-based matrix and a metal carbonized skeleton carbonized and coated on the silicon-based matrix, and the metal carbonized skeleton is prepared by carbonizing a metal organic framework material under an inert atmosphere at 1000-1200° C. In fact, there are silicon powder and a carbon skeleton coated on the outside of the silicon powder in the silicon-based matrix, and the carbon skeleton is prepared by carbonizing cellulose.

[0079] The present invention also provides an application of a metal-doped silicon-based negative electrode material prepared by the preparation method in any of the above embodiments in a lithium-ion battery. In fact, the negative electrode material can be mixed with a binder and a conductive agent to prepare a conductive slurry, and the conductive slurry can be coated on a current collector and dried to form a negative electrode, and the negative electrode, positive electrode, separator and electrolyte are assembled to prepare a lithium-ion battery.

[0080] Preparation Example 1

[0081] This preparation example 1 provides a method for preparing a silicon-based material, comprising the following steps:

[0082] Y1. After ultrasonically dispersing nano silicon powder with an average particle size of 50 nm and cellulose with an average particle size of 0.3 mm in deionized water at a mass ratio of 1:1, the mixture was separated by suction filtration and dried to constant weight in a vacuum drying oven at 70°C, and then transferred to a high-pressure atmosphere furnace, carbonized at 30 MPa and 350°C for 3 h, and then cooled to room temperature with the furnace, and crushed to obtain a silicon-carbon mixture;

[0083] Y2. Ultrasonic mixing of the silicon-carbon mixture in a methanol solution at a frequency of 20 kHz for 10 minutes to obtain a silicon-carbon mixed methanol suspension, and dropping the methanol solution of 1,3-propanedithiol dropwise into the silicon-carbon mixed methanol suspension, and controlling the dropping time to be 30 minutes. After the dropping is completed, stirring and mixing for 30 minutes, filtering and separating, washing the obtained solid with methanol, and drying in an oven at 50°C to constant weight to obtain a silicon-carbon composite; wherein the mass ratio of the silicon-carbon mixture to 1,3-propanedithiol is 1:0.1;

[0084] Y3. The silicon-carbon composite is placed in the furnace of a tubular furnace, and after nitrogen is introduced as a protective gas, the temperature of the tubular furnace is raised to 650°C at a rate of 5°C / min, and then the temperature is kept for carbonization treatment for 2 hours. After the furnace is cooled to room temperature, the silicon-based material is crushed to obtain a silicon-based material with an average particle size of 100 nm.

[0085] Preparation Example 2

[0086] This preparation example 2 provides a method for surface activation of a silicon-based material, comprising the following steps:

[0087] Y4. Dissolve isopropyl triisostearyl titanate (CAS: 61417-49-0, purchased from Jiangxi Chenguang New Materials Co., Ltd.) in anhydrous ethanol to prepare an active solution; then put the silicon-based material prepared in Preparation Example 1 into the active solution, mix it ultrasonically in a 40°C water bath environment, and then filter it under reduced pressure. After rinsing the obtained fixed material with anhydrous ethanol, dry it in an oven at 50°C to constant weight to obtain a surface-activated silicon-based material; wherein the mass ratio of the silicon-based material to isopropyl triisostearyl titanate is 1:0.08.

[0088] Preparation Example 3

[0089] This preparation example 3 provides a method for surface activation of a silicon-based material, comprising the following steps:

[0090] Y4. Preliminarily, N-(aminoethyl)-3-aminopropylmethyldimethoxysilane (KH-602, CAS: 3069-29-2) and anhydrous ethanol were uniformly mixed in a volume ratio of 1:10 to obtain an active solution; then, the silicon-based material obtained in Preparation Example 1 was added to the active solution, ultrasonically mixed in a 40°C water bath environment, and then vacuum filtered; after rinsing the obtained fixed material with anhydrous ethanol, it was dried in an oven at 50°C to constant weight to obtain a surface-activated silicon-based material; wherein, the mass ratio of the silicon-based material to N-(aminoethyl)-3-aminopropylmethyldimethoxysilane was 1:0.08.

[0091] Preparation Example 4

[0092] This preparation example 4 provides a preparation method for a metal organic framework nanosheet suspension, comprising the following steps: mixing a 1 mol / L cobalt chloride solution and a 5 mol / L 2-methylimidazole aqueous solution in a volume ratio of 1:1, ultrasonically mixing at a frequency of 20 kHz for 10 minutes, keeping warm in a 40°C water bath for 2 hours, filtering and separating, washing the precipitate with deionized water, and drying in a vacuum environment at 40°C to constant weight to obtain metal organic framework nanosheets, and then dispersing the obtained metal organic framework nanosheets in methanol to obtain a metal organic framework nanosheet suspension with a solid-liquid ratio of 0.08 g / mL.

[0093] Example 1

[0094] This embodiment 1 provides a method for preparing a metal-doped silicon-based negative electrode material, comprising the following steps:

[0095] S1. Add the surface activated silicon-based material prepared in Preparation Example 2 to the metal organic framework nanosheet suspension prepared in Preparation Example 4, and control the mass ratio of the surface activated silicon-based material to the metal organic framework nanosheet to be 1:0.1; ultrasonically treat at a frequency of 20 kHz for 10 minutes, keep warm at 50°C and stir at a speed of 200 rpm for 30 minutes, reduce pressure and filter, rinse the obtained solid with deionized water, and then dry at 50°C to constant weight to obtain a composite precursor;

[0096] S2, adding the composite precursor into the melamine solution, and controlling the mass ratio of the composite precursor to melamine to be 1:0.25; ultrasonically mixing at a frequency of 20 kHz for 10 minutes, and then keeping warm in a 45°C water bath environment for 1 hour, and after vacuum filtration, washing the obtained solid with anhydrous ethanol, and drying in a 40°C hot air drying oven to constant weight to obtain a composite intermediate;

[0097] S3. After ultrasonically mixing the composite intermediate in a cobalt chloride aqueous solution at a frequency of 20 kHz for 10 minutes, a 2-methylimidazole aqueous solution was added dropwise in a water bath environment at 50°C and 200 rpm, and the mass ratio of the composite intermediate, cobalt ions, and 2-methylimidazole was controlled to be 1:0.25:0.07; after the addition was completed, the mixture was stirred and kept warm in a 50°C water bath environment for 30 minutes, filtered and separated, and the precipitate was rinsed with deionized water, and then dried in a 50°C hot air drying oven to constant weight to obtain a doped intermediate;

[0098] S4. Place the doped intermediate in the furnace of a tubular furnace. Heat the tubular furnace to 120°C at a rate of 5°C / min in an air atmosphere, and then keep it warm for pre-sintering for 1 hour. After argon is introduced into the tubular furnace for gas replacement, heat the tubular furnace to 1100°C at a rate of 5°C / min in an argon atmosphere, and then calcine for 2 hours. After cooling to room temperature in the furnace, the metal-doped silicon-based negative electrode material is obtained.

[0099] Example 2

[0100] This embodiment 2 provides a method for preparing a metal-doped silicon-based negative electrode material, which is different from the embodiment 1 in that the surface-activated silicon-based material prepared in the preparation example 3 is used in step S1.

[0101] Example 3

[0102] This embodiment 3 provides a method for preparing a metal-doped silicon-based negative electrode material, which is different from embodiment 1 in that in step S3, after the composite intermediate is ultrasonically mixed in a zinc chloride aqueous solution at a frequency of 20 kHz for 10 minutes, a 2-methylimidazole aqueous solution is added dropwise in a water bath environment at 50°C and 200 rpm, and the mass ratio of the composite intermediate, zinc ions, and 2-methylimidazole is controlled to be 1:0.25:0.07.

[0103] Comparative Example 1

[0104] This comparative example 1 provides a method for preparing a metal-doped silicon-based negative electrode material, which is different from Example 1 in that in step S1, the silicon-based material prepared in Preparation Example 1 is added to the metal-organic framework nanosheet suspension prepared in Preparation Example 4, and the mass ratio of the silicon-based material to the metal-organic framework nanosheet is controlled to be 1:0.1.

[0105] Comparative Example 2

[0106] This comparative example 2 provides a method for preparing a metal-doped silicon-based negative electrode material, which is different from Example 1 in that step S2 is not performed. In step S3, the composite precursor is directly ultrasonically mixed in a cobalt chloride aqueous solution at a frequency of 20 kHz for 10 minutes, and then a 2-methylimidazole aqueous solution is added dropwise in a water bath environment at 50°C and 200 rpm, and the mass ratio of the composite precursor, cobalt ions, and 2-methylimidazole is controlled to be 1:0.25:0.07.

[0107] Comparative Example 3

[0108] Comparative Example 3 provides a method for preparing a metal-doped silicon-based negative electrode material, which is different from Example 1 in that step S3 is not performed, and in step S4 the composite intermediate is directly placed in a tubular furnace for temperature-raising calcination.

[0109] Performance Testing

[0110] The metal-doped silicon-based negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used as active materials, LA133 was used as a binder, acetylene black was used as a conductive agent, and were uniformly mixed in a mass ratio of 8:1:1, coated on a copper foil, vacuum dried, and then rolled, and cut into negative electrode sheets with a diameter of 14 mm, metallic lithium was used as a positive electrode sheet, lithium hexafluorophosphate was used as an electrolyte, and a polypropylene microporous membrane was used as a separator, and button-type lithium batteries were assembled in a glove box for the following electrochemical performance tests.

[0111] First coulombic efficiency test: at room temperature, discharge at a current density of 0.1C to 0.01V, then discharge at a current density of 0.02C to 0.005V, and finally charge at a current density of 0.1C to 1.5V. The capacity when charged to 1.5V is measured as the first reversible specific capacity, and the first coulombic efficiency is calculated. The results are shown in Table 1 below.

[0112] Cycle performance test: constant current charge and discharge were performed at room temperature with a current density of 0.1C, and the charge and discharge voltage was limited to 0.005V-1.5V. The charge specific capacity after 100 cycles was measured, and the capacity retention rate after 100 cycles was calculated. The results are shown in Table 1 below.

[0113] Table 1 Electrochemical performance test results

[0114] ,

[0115] Combining Example 1 with Example 2 and Table 1, it can be seen that the use of different coupling agents to modify the surface of the silicon-based material can improve the bonding stability between the surface of the silicon-based material and the metal organic framework nanosheets, and the obtained negative electrode material can exhibit higher capacity and cycle stability after being applied to lithium-ion batteries.

[0116] In combination with Examples 1 to 3, and from Table 1, it can be seen that the doping of homogeneous metal-organic framework nanoparticles on the metal-organic framework nanosheets on the surface of the composite intermediate has better bonding performance, which is beneficial to improving the structural stability of the negative electrode material, thereby showing higher cycle stability.

[0117] Combining Example 1 with Comparative Example 1, and from Table 1, it can be seen that in Comparative Example 1, the silicon-based material was not subjected to surface activation treatment. Although the metal organic framework nanosheets could also be coated, the bonding strength decreased significantly, which was manifested as a significant decrease in the cycle stability. This indicates that surface treatment of the silicon-based material in advance can effectively improve the bonding stability between the silicon-based material and the metal organic framework nanosheets.

[0118] Combining Example 1 with Comparative Example 2, and as can be seen from Table 1, in Comparative Example 2, the composite precursor was not subjected to surface melamine coating treatment, and when the metal organic framework nanoparticles were formed in step S3, it was easy to continue the growth of the nanosheets along the direction of the metal organic framework nanosheets, and it was difficult to play the role of filling the pores. Therefore, the pore structure on the surface of the silicon-based material was larger and the structural stability was poor, which was manifested as a significant decrease in the cycle stability.

[0119] Combining Example 1 with Comparative Example 3, and from Table 1, it can be seen that in Comparative Example 3, metal organic framework nanoparticles are not grown on the surface of the composite intermediate, and only melamine is used to coat the surface. The binding force of melamine between the metal organic framework nanosheet layers can be used to reduce the pore size and further increase the bonding strength between the metal organic framework layer and the silicon-based material, thereby improving the cycle stability.

[0120] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a metal-doped silicon-based negative electrode material, characterized in that: include: The silicon-based material is surface-treated in a titanate coupling agent and / or a nitrogen-containing coupling agent to obtain a surface-activated silicon-based material; The surface activated silicon-based material is stirred and mixed in a metal organic framework nanosheet suspension, and then separated and dried to obtain a composite precursor; the composite precursor is stirred and mixed in a coating solution, and then separated and dried to obtain a composite intermediate; after stirring and mixing the composite intermediate in a transition metal solution, an organic ligand is added dropwise, stirred for reaction, and then separated and dried to obtain a doped intermediate; the doped intermediate is pre-sintered in an oxygen-containing atmosphere at 100° C.-150° C. for 0.5 h-1 h, and then calcined in an inert atmosphere at 1000° C.-1200° C. and cooled to obtain a metal-doped silicon-based negative electrode material; the preparation method of the silicon-based material comprises: Silicon powder and cellulose are stirred and mixed, then carbonized and crushed to obtain a silicon-carbon mixture; the silicon-carbon mixture is ultrasonically mixed in an alcohol solution, a cross-linking agent is added, stirred and mixed, and then separated and dried to obtain a silicon-carbon composite; the silicon-carbon composite is carbonized at 600°C-700°C and then crushed to obtain a silicon-based material; the cross-linking agent is one of 1,3-propanedithiol, 1,5-pentanedithiol, and 1,9-nonanedithiol; the titanate coupling agent includes one of triisostearyl isopropyl titanate and isopropoxy tricarboxylic acid titanate; the nitrogen-containing coupling agent includes 3-piperazinylpropyl methyl dimethoxy silane, N -(aminoethyl)-3-aminopropylmethyldimethoxysilane; the solute in the coating solution includes melamine.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon powder to the cellulose is 1:(1-1.5).

3. The preparation method according to claim 1, characterized in that: Silicon powder and cellulose are mixed and then carbonized and crushed at 10MPa-50MPa and 300℃-400℃.

4. The preparation method according to claim 1, characterized in that: The alcohol solution includes one of methanol and ethanol.

5. The preparation method according to claim 1, characterized in that: The solid-to-liquid ratio of the silicon-carbon mixture in the alcohol solution is 0.05 g / mL-0.08 g / mL.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon-carbon mixture to the cross-linking agent is 1:(0.1-0.2).

7. The preparation method according to claim 1, characterized in that: The average particle size of the silicon-based material is 50nm-100nm.

8. The preparation method according to claim 1, characterized in that: The silicon-based material is immersed in an active solution in which a titanate coupling agent and / or a nitrogen-containing coupling agent is dissolved, and then separated and dried to obtain the silicon-based material after surface activation.

9. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon-based material to the coupling agent is 1:(0.05-0.10), and the coupling agent is a titanate coupling agent and / or a nitrogen-containing coupling agent.

10. The preparation method according to claim 1, characterized in that: The mass ratio of the surface activated silicon-based material to the metal organic framework nanosheets in the metal organic framework nanosheet suspension is 1:(0.1-0.2).

11. The preparation method according to claim 1, characterized in that: The length of the metal organic framework nanosheets in the metal organic framework nanosheet suspension is 1 μm-10 μm and the thickness is 50 nm-200 nm.

12. The preparation method according to claim 1, characterized in that: The solvent in the metal organic framework nanosheet suspension includes one of methanol and ethanol.

13. The preparation method according to claim 1, characterized in that: The mass ratio of the composite precursor to the solute in the coating solution is 1:(0.2-0.3).

14. The preparation method according to claim 1, characterized in that: The composite precursor was stirred and mixed in the coating solution at 40°C-50°C.

15. The preparation method according to claim 1, characterized in that: The composite precursor is dispersed in the coating solution by ultrasonication.

16. The preparation method according to claim 1, characterized in that: The composite precursor is stirred and mixed in the coating solution, separated and dried in a vacuum environment at 60° C.-80° C.

17. The preparation method according to claim 1, characterized in that: The transition metal element in the transition metal solution includes one of cobalt, copper, titanium, manganese, zinc and platinum.

18. The preparation method according to claim 1, characterized in that: The organic ligand includes one of 2-methylimidazole, terephthalic acid, and 2,5-thiophenedicarboxylic acid.

19. The preparation method according to claim 1, characterized in that: The mass ratio of the composite intermediate, the transition metal element in the transition metal solution, and the organic ligand is 1:(0.2-0.3):(0.05-0.08).

20. The preparation method according to claim 1, characterized in that: The oxygen volume fraction in the oxygen-containing atmosphere is 10%-100%.

21. The preparation method according to claim 1, characterized in that: The doped intermediate is heated to 100° C.-150° C. at a rate of 1° C. / min-10° C. / min in an oxygen-containing atmosphere.

22. The preparation method according to claim 1, characterized in that: The doped intermediate is pre-sintered in an oxygen-containing atmosphere at 100° C.-150° C. for 0.5 h-1 h, and then heated to 1000° C.-1200° C. at a rate of 1° C. / min-10° C. / min in an inert atmosphere.

23. The preparation method according to claim 1, characterized in that: Calcinate at 1000℃-1200℃ in inert atmosphere for 2h-3h.

24. A metal-doped silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 23.

25. Use of the metal-doped silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 23 in a lithium-ion battery.

Citation Information

Patent Citations

  • Method for preparing silicon carbide alloy negative electrode material for lithium ion battery

    CN102376944A